Search for and functional annotation of multi-domain PLA2 family proteins in flatworms - M. E. Bocharnikova; I. I. Turnaev; D. A. Afonnikov (Вавиловский журнал генетики и селекции)
The phospholipase A2 (PLA2) is a superfamily of hydrolases that catalyze the hydrolysis of phospholipids and play a key role in many molecular processes in the cells and the organism as a whole. This family consists of 16 groups divided into six main types. PLA2 were first isolated from venom toxins and porcine pancreatic juice. The study of these enzymes is currently of great interest, since it has been shown that a number of PLA2 are involved in the processes of carcinogenesis. PLA2 enzymes were characterized in detail in model organisms and humans. However, their presence and functional role in non-model organisms is poorly understood. Such poorly studied taxa include flatworms, a number of species of which are human parasites. Several PLA2 genes have previously been characterized in parasitic flatworms and their possible role in parasite-host interaction has been shown. However, no systematic identification of the PLA2 genes in this taxon has been carried out. The paper provides a search for and a comparative analysis of PLA2 sequences encoded in the genomes of flatworms. 44 species represented by two free-living and 42 parasitic organisms were studied. The analysis was based on identification of orthologous groups of protein-coding genes, taking into account the domain structure of proteins. In flatworms, 12 of the 13 known types of animal A2 phospholipases were found, represented by 11 orthologous groups. Some phospholipases of several types fell into one orthologous group, some types split into several orthogroups in accordance with their domain structure. It has been shown that phospholipases A2 of the calcium-independent type, platelet-activating phospholipases from group G8 and lysosomal phospholipases from group G15 are represented in all large taxa of flatworms and the vast majority of the species studied by us. In free-living flatworms PLA2 genes have multiple copies. In parasitic flatworms, on the contrary, loss of genes occur specifically in individual taxa specifically for groups or subfamilies of PLAs. An orthologous group of secreted phospholipases has been identified, which is represented only in Digenea and this family has undergone duplications in the genomes of opisthorchids. Interestingly, a number of experimental studies have previously shown the effect of Clonorchis sinensis proteins of this orthogroup on the cancer transformation of host cells. Our results made it possible for the first time to systematically identify PLA2 sequences in flatworms, and demonstrated that their evolution is subject to gene loss processes characteristic of parasite genomes in general. In addition, our analysis allowed us to identify taxon-specific processes of duplication and loss of PLA2 genes in parasitic organisms, which may be associated with the processes of their interaction with the host organism.